Cu-catalyzed controllable C–H mono-/di-/triarylations of imidazolium salts for ionic functional materials. Issue 24 (10th March 2017) - Li, Shiqing; Tang, Junbin; Zhao, Yinsong; Jiang, Ruyong; Wang, Tianbao; Gao, Ge; You, Jingsong
Abstract : The first Cu-catalyzed direct C–H mono-, di- and triarylations of imidazolium salts with aryl iodides/bromides are reported. Abstract : Herein the Cu-catalyzed direct C–H mono-, di- and triarylations of imidazolium salts with aryl iodides/bromides are accomplished for the first time. The unprecedented alkenylation and alkynylation are also realized using alkenyl and alkynyl iodides, respectively. Moreover, triarylated imidazolium salts with different substituents can be accessed in a modular and one-pot manner. This protocol provides an efficient tool for the assembly of diverse imidazolium-based ionic functional materials. As applicable examples, an electrochromic bisbenzimidazolium salt7 and a photochromic triarylimidazolium salt8 are easily obtained.